Boosting the cell performance of the SiOx@C anode material via rational design of a Si‐valence gradient. Issue 2 (18th August 2021) - Tao, Jianming; Yan, Zerui; Yang, Jiangshao; Li, Jiaxin; Lin, Yingbin; Huang, Zhigao
Abstract: Relieving the stress or strain associated with volume change is highly desirable for high‐performance SiO x anodes in terms of stable solid electrolyte interphase (SEI)‐film growth. Herein, a Si‐valence gradient is optimized in SiO x composites to circumvent the large volume strain accompanied by lithium insertion/extraction. SiO x @C annealed at 850°C has a gentle Si‐valence gradient along the radial direction and excellent electrochemical performances, delivering a high capacity of 506.9 mAh g −1 at 1.0 A g −1 with a high Coulombic efficiency of ~99.8% over 400 cycles. Combined with the theoretical prediction, the obtained results indicate that the gentle Si‐valence gradient in SiO x @C is useful for suppressing plastic deformation and maintaining the inner connection integrity within the SiO x @C particle. Moreover, a gentle Si‐valence gradient is expected to form a stress gradient and affect the distribution of dangling bonds, resulting in local stress relief during the lithiation/delithiation process and enhanced Li‐ion kinetic diffusion. Furthermore, the lowest interfacial stress variation ensures a stable SEI film at the interface and consequently increases cycling stability. Therefore, rational design of a Si‐valence gradient in SiO x can provide further insights into achieving high‐performance SiO x anodes with large‐scale production. Abstract : It is highly desirable to develop a novel internal‐stress‐relief strategy to suppress SiO x expansion via design and optimization of Si valence in SiO x composites for high‐energy‐density lithium‐ion batteries. In our work, enhanced electrochemical performances of SiO x are obtained via optimizing the Si‐valence gradient from the viewpoint of stress evolution upon cycling.